Obstructive eustachian tube dysfunction - current diagnosis and treatment - Oehlandt, Heidi (fi=Turun yliopisto|en=University of Turku|, 2023)
The Eustachian tube (ET) connects the middle ear (ME) to the nasopharynx and has a vital role in ME health. Functional obstructive Eustachian tube dysfunction (OETD) is a result of an inadequate opening of the ET. The symptoms of OETD, however, are unspecific, posing a need for objective ET measurements. One of the most objective methods to test ET opening is tubomanometry (TMM), which has been shown to have sufficiently high specificity and sensitivity to OETD. Nevertheless, information on the technical success rate and factors affecting the results is almost nonexistent. Proper diagnosis has high significance nowadays, as there is a surgical treatment option for OETD, balloon Eustachian tuboplasty (BET). BET has in many studies proven to be effective and safe. Despite this, more studies are needed on its use in different patient groups. We studied the clinical use of TMM in OETD diagnostics by assessing the technical success rate of the TMM measurements in a retrospective cohort from Helsinki University Hospital in 2016‒2020. The success rate (91%) was evaluated to be sufficiently high for clinical diagnostics. In addition, we evaluated factors affecting the TMM results; the only patient-related characteristic to have an effect seemed to be a pollen allergy. We also examined the efficacy and safety of BET in different patient groups: children, baro-challenge-induced ETD patients, OETD patients, and as part of other ear surgery. Therefore, all consecutive patients from Turku University Hospital during 2013‒2016 and baro-challenge-induced ETD patients from Helsinki University Hospital during 2011‒2020 treated with BET were retrospectively evaluated. Questionnaires showed long-term improvement in all these groups. No major complications were encountered. An additional systematic review revealed that studies on baro-challenge-induced ETD were heterogeneous, with a small study sample and varying improvements in outcome measures. In conclusion, TMM appears to be a reliable and practical diagnostic tool for OETD patients. Our results on BET compliments the existing studies suggesting long-term efficacy and safety also in different patient groups.